2014
DOI: 10.1097/ss.0000000000000096
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Organic Carbon via Chemical Interactions with Fe and Al Oxides in Gley Soils

Abstract: The importance of soil organic carbon (SOC) stabilization via chemical interactions with Fe and Al oxide minerals within gley soils remains unclear. Changes in the proportions of Fe/Al oxides and SOC and N contents associated with Fe/Al oxides within the profiles of gley soils under contrasting hydrological regimes and freely draining control soils from Harwood Forest (northeast England) were investigated. Sequential selective dissolution techniques were used to measure Fe/Al oxide crystallinity and explore wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Other than soil pH, both Al d contents and BGB have strong positive effects on the abundance of all compound groups in the alpine grassland soils ( p < 0.05; Figures and ). The former trend can be attributed to the strong sorption capacity of reactive Al oxides for soil aliphatic components (Cloy et al, ; Fleury et al, ; Mikutta et al, ; Ulrich et al, ) and carbohydrates (Cloy et al, ; Miltner & Zech, ), contributing to their enhanced preservation in the soil. By comparison, the latter trend is, to a large extent, a reflection that plant roots are a key source of solvent‐extractable compounds in the alpine grassland soils and that such input signals are not significantly altered by decomposition processes, which are inhibited by low temperatures in the alpine regions (Baumann et al, ; Liu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Other than soil pH, both Al d contents and BGB have strong positive effects on the abundance of all compound groups in the alpine grassland soils ( p < 0.05; Figures and ). The former trend can be attributed to the strong sorption capacity of reactive Al oxides for soil aliphatic components (Cloy et al, ; Fleury et al, ; Mikutta et al, ; Ulrich et al, ) and carbohydrates (Cloy et al, ; Miltner & Zech, ), contributing to their enhanced preservation in the soil. By comparison, the latter trend is, to a large extent, a reflection that plant roots are a key source of solvent‐extractable compounds in the alpine grassland soils and that such input signals are not significantly altered by decomposition processes, which are inhibited by low temperatures in the alpine regions (Baumann et al, ; Liu et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Surface hydroxyl (−OH) groups of the crystalline Fe/Al phase can directly bind OM compounds through inner-sphere complexations via ligand exchange . This strong inner-sphere complexation contributes to the long-term OM preservation from microbial decomposition. , …”
Section: Resultsmentioning
confidence: 99%
“…67 This strong inner-sphere complexation contributes to the long-term OM preservation from microbial decomposition. 52,68 Molecular Composition of Extractable OM Fractions. The chemical characteristics of OM in the water-soluble fraction were very diverse, with H/C ranging from 0.30 to 2.23 and O/C ranging from 0.02 to 1.18 (Figure 4).…”
Section: ■ Introductionmentioning
confidence: 99%
“…The apparent higher amount of adsorbed Dextran is related to the presence of nanoFeH on the surface of illite platelets, which leads to the following questions: what is the exact mechanism of aggregate formation and what is the exact role played by nanoFeH? The affinity of iron oxides for organic matter was reported in numerous studies (Reinhardt and Wilkinson, 2004;Cloy et al, 2014;Vindedahl et al, 2016;Sowers et al, 2018b), so that it is likely that the presence of nanoFeH enhanced Dextran adsorption. For Fe-montmorillonite heteroaggregates (Ji et al, 2004), it was suggested that the presence of FeH reduced the charge and electric field of clay particles.…”
Section: Influence Of Nanofeh On Illite-dextran Interactionsmentioning
confidence: 94%